FDI, Global Value Chains, and Local Sourcing in Developing Countries - Amendolagine, Vito (IMF Working Papers; Working Paper ;, 2017)
The local sourcing of intermediate products is one the main channels for foreign direct investment (FDI) spillovers. This paper investigates whether and how participation and positioning in the global value chains (GVCs) of host countries is associated to local sourcing by foreign investors. Matching two firm-level data sets of 19 Sub-Saharan African countries and Vietnam to country-sector level measures of GVC involvement, we find that more intense GVC participation and upstream specialization are associated to a higher share of inputs sourced locally by foreign investors. These effects are larger in countries with stronger rule of law and better education.